2005
DOI: 10.1242/dev.01644
|View full text |Cite
|
Sign up to set email alerts
|

Delta-Notch signalling controls commitment to a secretory fate in the zebrafish intestine

Abstract: The transparency of the juvenile zebrafish and its genetic advantages make it an attractive model for study of cell turnover in the gut. BrdU labelling shows that the gut epithelium is renewed in essentially the same way as in mammals: the villi are lined with non-dividing differentiated cells, while cell division is confined to the intervillus pockets. New cells produced in the pockets take about 4 days to migrate out to the tips of the villi, where they die. We have generated monoclonal antibodies to identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
216
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 235 publications
(237 citation statements)
references
References 43 publications
21
216
0
Order By: Relevance
“…During the preparation of this manuscript, three other relevant reports were published (31)(32)(33). These studies support our conclusion that Notch regulates the secretory-absorptive cell fate decision in intestinal development.…”
Section: Labeling Adult Intestinal Progenitor Cells and Misexpressionsupporting
confidence: 84%
“…During the preparation of this manuscript, three other relevant reports were published (31)(32)(33). These studies support our conclusion that Notch regulates the secretory-absorptive cell fate decision in intestinal development.…”
Section: Labeling Adult Intestinal Progenitor Cells and Misexpressionsupporting
confidence: 84%
“…A comparable effect on biliary development of the oc3 knockdown was revealed by immunstainings with a monoclonal antibody (2F11; Crosnier et al, 2005) that detects biliary epithelial cell bodies and the proximal regions of the ducts arising from these cells. These stainings showed abnormal biliary epithelial cell morphology and a reduced ductal network .…”
Section: Antisense Knockdown Reveals a Role For Onecut3 In Zebrafish mentioning
confidence: 74%
“…Staining using 2F11 (Crosnier et al, 2005) was performed similarly, at a dilution of 1:1,000. Images were obtained using confocal microscopy of whole-mount livers.…”
Section: Immunohistochemistry and Quantificationmentioning
confidence: 99%
“…Though Notch is best known for its role in lateral inhibition, activation of this pathway also promotes cell fate (Irvine 1999;Gaiano et al 2000;Grandbarbe et al 2003). Recent studies have shown that Notch signaling regulates a broad range of patterning processes during embryonic and postnatal development (Hitoshi et al 2002;Krebs et al 2003, Raya et al 2003Burns et al 2005;Crosnier et al 2005;Duncan et al 2005;Fre et al 2005;van Es et al 2005; for reviews, see Lai 2004;Yoon and Gaiano 2005).…”
mentioning
confidence: 99%